MASNet: mixed attention Siamese network for visual object tracking - Jianwei Zhang; Zhichen Zhang; Huanlong Zhang; Jingchao Wang; He Wang; Menya Zheng (Systems Science & Control Engineering, 2024)
Most Siamese-based trackers adopt correlation operation to perform similarity matching on feature fusion of template branch and search branch. However, the correlation operation directly uses the template feature to slide the window on the search area feature, and it is difficult to distinguish the target and background information when encountering similar target interference and background clutter, which can easily lead to tracking failure. In this paper, a mixed attention Siamese Network (MASNet) is proposed, which neatly integrates the modelling of global information and mutual information into the Siamese tracking framework. Specifically, through the learnable attention module, the local and global dependencies are adaptively integrated, and the rich context information is captured to improve the discrimination of the network for similar targets. After that, the correlation of the context information of the two branches is aggregated and adaptively encoded into the two branches, which makes up for the shortcomings of single correlation operation. In addition, the framework adopts a three-layer feature fusion method, which enables the tracker to better adapt to object deformation and similar object interference. Extensive experiments on OTB100, UAV123, GOT-10k and LaSOT show that the proposed tracking method achieves comparable performance to the advanced trackers.